Messianic mysticism : Moses Hayim Luzzatto and the Padua school - Tishby, Isaiah (Littman library of Jewish civilization (Series), 2008)
Tishby's seminal study, based largely on manuscripts he discovered, shows Luzzatto as one of the most profound mystics in the history of Jewish culture.